A systematic review of the effectiveness of discharge care bundles for patients with COPD. Issue 1 (9th September 2016) - Ospina, Maria B; Mrklas, Kelly; Deuchar, Lesly; Rowe, Brian H; Leigh, Richard; Bhutani, Mohit; Stickland, Michael K
Abstract : Background: A COPD discharge bundle is a set of evidence-based practices aimed at improving patient outcomes after discharge from acute care settings following an exacerbation. We conducted a systematic review on the effectiveness of COPD discharge bundles and summarised their individual care elements. Methods: Biomedical electronic databases and clinical trial registries were searched from database inception through April 2016 to identify experimental studies evaluating care bundles offered to patients with COPD at discharge. Random-effects meta-analyses of clinical trials data were conducted for hospital readmissions, mortality, and quality of life (QoL). Results: The review included 14 studies (5 clinical trials, 7 uncontrolled trials, and 2 interrupted time series). A total of 26 distinct elements of care were included in the bundles of individual studies. Evidence from four clinical trials with moderate-to-high risk of bias showed that COPD discharge bundles reduced hospital readmissions (pooled risk ratio (RR): 0.80; 95% CI 0.65 to 0.99). There was insufficient evidence that care bundles influence long-term mortality (RR: 0.74; 95% CI 0.43 to 1.28; four trials) or QoL (mean difference in St. George's Respiratory Questionnaire: 1.84; 95% CI −2.13 to 5.8). Conclusions: Discharge bundles for patients with COPD led to fewer readmissions but did not significantly improve mortality or QoL. Future studies should employ higher quality research methods, fully report care bundle elements, implementation strategies and intervention fidelity to better evaluate the effectiveness of packaging evidence-based interventions together to improve outcomes of patients with COPD discharged from acute care settings.